PENGEMBANGAN MODEL LATIHAN UNTUK MENINGKATKAN KECEPATAN TENDANGAN AP CHAGI PADA TAEKWONDO UNIT KEGIATAN MAHASISWA UNIVERSITAS LAMPUNG - Rahma Cahyani; Candra Kurniawan; Riyan Jaya Sumantri; Joan Siswoyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop and examine the effectiveness of an agility ladder training model in improving the speed of ap chagi kicks among Taekwondo athletes of the Student Activity Unit at the University of Lampung. The research employed a Research and Development (R&D) approach, including needs analysis, product design, expert validation, product revision, and field testing. The research subjects consisted of taekwondo and learning experts as validators, as well as Taekwondo athletes as trial participants. Data were collected using expert validation questionnaires and ap chagi kick speed tests. Data analysis was conducted using descriptive quantitative techniques with percentage calculations to determine the feasibility and effectiveness of the developed training model. The results indicated that the agility ladder training model was considered feasible based on expert evaluations and effective in improving athletes’ ap chagi kick speed. Therefore, the developed training model can be applied as an alternative training method to enhance taekwondo kick performance in university settings.